2022
DOI: 10.18632/aging.203817
|View full text |Cite
|
Sign up to set email alerts
|

Hesperidin suppresses ERS-induced inflammation in the pathogenesis of non-alcoholic fatty liver disease

Abstract: Recent studies have confirmed that endoplasmic reticulum stress (ERS) and inflammation play critical roles in the development of . ER is an essential cellular organelle that regulates protein synthesis, folding, and post-translational modification www.aging-us.com

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 47 publications
(50 reference statements)
0
10
0
Order By: Relevance
“…It has antioxidation, inhibits inflammation, and improves the molecular mechanism of glucose and lipid metabolism through AMPK/peroxisome proliferator-activated receptor-Gamma coactivator 1 Alpha (PGC-1a) and PPAR signaling pathways (138)(139)(140). In addition, studies have shown that HSP can significantly inhibit endoplasmic reticulum stress in oxidative stress in NAFLD models in vivo and in vitro (141). In this systematic review, Yari et al found that compared with the control group, hesperidin+flaxseed, hesperidin, and flaxseed could reduce plasma ALT levels and HOMA-IR, fasting blood glucose, and fatty liver index.…”
Section: Hesperidinmentioning
confidence: 91%
“…It has antioxidation, inhibits inflammation, and improves the molecular mechanism of glucose and lipid metabolism through AMPK/peroxisome proliferator-activated receptor-Gamma coactivator 1 Alpha (PGC-1a) and PPAR signaling pathways (138)(139)(140). In addition, studies have shown that HSP can significantly inhibit endoplasmic reticulum stress in oxidative stress in NAFLD models in vivo and in vitro (141). In this systematic review, Yari et al found that compared with the control group, hesperidin+flaxseed, hesperidin, and flaxseed could reduce plasma ALT levels and HOMA-IR, fasting blood glucose, and fatty liver index.…”
Section: Hesperidinmentioning
confidence: 91%
“…The tissues were observed using an optical microscope (Carl Zeiss AG). Finally, the relative level of lipids was calculated as the Oil Red O‐stained area divided by total cell area and analyzed by ImageJ software [23].…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, hesperidin activated AMPK signaling pathway (Chen et al, 2022), upregulated PI3K/ AKT-Nrf2 signaling (J. Li, Wang, et al, 2021), and inhibited ER stressinduced inflammatory response (Xie et al, 2022).…”
Section: Hesperidinmentioning
confidence: 99%
“…On the one hand, hesperidin altered the makeup of the intestinal microbiota and diversified specific genera, such as Bacteroidota (X. Li, Yao, et al, 2022). On the other hand, hesperidin activated AMPK signaling pathway (Chen et al, 2022), upregulated PI3K/AKT‐Nrf2 signaling (J. Li, Wang, et al, 2021), and inhibited ER stress‐induced inflammatory response (Xie et al, 2022).…”
Section: Mechanisms Of Polyphenolic Compounds Protect Against Hepatic...mentioning
confidence: 99%